IMPACT ON BRITISH INFLUENCE OF COLONIALISM IN INDIAN HISTORY WRITING - M. Nagalaxmi, Dr. Siraj Khan (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
British Imperialism influences Indian History writing. Britishers tried to prove that India has no history, and therefore, Indians must be remained slave. All English Historians see contemporary Indian Society of India a low and out casted. They wanted to justify their rule over India and for this purpose they started distorted the Indian rich History by giving false information which was fullfilling their personal malivers to plunder the India. From very begining many Nationalist Historians raised their voice against these British Historians and tried to brought about real rich history of India into light.